Pengaruh locus of control internal terhadap kinerja karyawan dengan etika kerja islam sebagai variabel moderasi - Risahayu Umiyaroh; Tetra Hidayati; Rabiatul Adawiyah (Jurnal Ilmu Ekonomi Mulawarman (JIEM), 2018)
This study aims to examine the effect of internal locus of control on employee performance with Islamic work ethics as a moderating variable. The first hypothesis examines whether the internal locus of control affects employee performance. The second hypothesis examines whether Islamic work ethics affects employee performance. The third hypothesis examines whether Islamic work ethics is a moderating variable in terms of internal locus of control and employee performance. Population in this research is all employees of Bank Syariah Mandiri Branch Office of Samarinda. In determining the number of samples, the authors used a saturated census (census) technique in which all members of the population were used as a total sample size of 40 people. Research data were collected by survey method and analyzed using moderation regression with the help of data management system computerized program SPSS 23. From the results of the study showed that the internal locus of control positive effect on employee performance. And the Islamic work ethic also shows a positive influence on employee performance. Another result that can be concluded is that Islamic work ethic variable is a moderation variable and at the same time become independent variable (predictor) in relation between locus of control internal and employee performance. Internal locus of control variable is an independent variable (predictor) in relation to employee performance.